Underrepresentation of elderly people in randomised controlled trials. The example of trials of 4 widely prescribed drugs. - Cécile Konrat; Isabelle Boutron; Ludovic Trinquart; Guy-Robert Auleley; Philippe Ricordeau; Philippe Ravaud (PLoS ONE, 2012)
BACKGROUND: We aimed to determine the representation of elderly people in published reports of randomized controlled trials (RCTs). We focused on trials of 4 medications--pioglitazone, rosuvastatin, risedronate, and valsartan-frequently used by elderly patients with chronic medical conditions. METHODS AND FINDINGS: We selected all reports of RCTs indexed in PubMed from 1966 to April 2008 evaluating one of the 4 medications of interest. Estimates of the community-based "on-treatment" population were from a national health insurance database (SNIIR-AM) covering approximately 86% of the population in France. From this database, we evaluated data claims from January 2006 to December 2007 for 1,958,716 patients who received one of the medications of interest for more than 6 months. Of the 155 RCT reports selected, only 3 studies were exclusively of elderly patients (2 assessing valsartan; 1 risedronate). In only 4 of 37 reports (10.8%) for pioglitazone, 4 of 22 (18.2%) for risedronate, 3 of 29 (10.3%) for rosuvastatine and 9 of 67 (13.4%) for valsartan, the proportion of patients aged 65 or older was within or above that treated in clinical practice. In 62.2% of the reports for pioglitazone, 40.9% for risedronate, 37.9% for rosuvastatine, and 70.2% for valsartan, the proportion of patients aged 65 or older was lower than half that in the treated population. The representation of elderly people did not differ by publication date or sample size. CONCLUSIONS: Elderly patients are poorly represented in RCTs of drugs they are likely to receive.